Lift mechanics of downhill skiing and snowboarding - Wu, Q.; Igci, Y.; Andreopoulos, Y.; Weinbaum, S. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study is conducted to develop a simplified mathematical model to describe the lift mechanics of downhill skiing and snowboarding, where the lift contributions due to both the transiently trapped air and the compressed solid phase (snow crystals) are determined. To our knowledge, this is the first time that anyone has attempted to realistically estimate the relative contribution of the transiently trapped air to the total lift in skiing and snowboarding.